Hubungan Pengetahuan Ibu tentang Stimulasi Dini dengan Perkembangan Motorik pada Anak Usia 6-24 bulan di Kecamatan Mayang Kabupaten Jember - Ayu Yoniko Christiari; Ramzi Syamlan; Irawan Fajar Kusuma (UPT Percetakan dan Penerbitan Universitas Jember, 2013)
Motoric development in the first two years is important for the children's cognitive function in the future. Mother has to know about the child development stage and early stimulation to optimalize child motoric development. The aim of the research was to assess the relationship between mother's knowledge of early stimulation and motoric development in 6 – 24 months old children. This research was conducted in Mayang sub-district of Jember in January until February 2013 by using the matched case control study. The respondents were 259 children in age of 6 – 24 months and their mother. Children with normal motoric development were included in the control group and children with suspected motoric development delay were included in the case group. Mother from both groups were examined retrospectively about their knowledge of early stimulation. Data were analyzed using Marginal Homogeneity test and Conditional Logistic Regression test. Bivariate analysis showed a significance value (p=0,000) and the Odds Ratio value 4,950. It was concluded that there was a significant relationship between mother's knowledge of early stimulation and motoric development in 6 – 24 months old children and children with low knowledge in early stimulation-mother have a higher risk of suspected motoric development delay. Keywords: child development, early stimulation, mother's knowledge, motoric development.